The impact of allergic rhinitis on gastrointestinal disorders among young adults. Issue 1 (17th February 2019) - Ho, Sai‐Wai; Lin, Ching‐Pin; Ku, Min‐Sho
Abstract: Background: An association between allergic rhinitis (AR) and digestive diseases (DDs) has been reported; however, studies have only focused on the prevalence of DDs in populations of patients with AR. In individuals with specific DDs, the impact of AR on the frequency of clinical visits for each DD has not been studied. Moreover, the association between topical steroid usage for AR and DDs has not been investigated. Methods: Data from 16 526 men and 18 438 women, aged 21 to 30 years, were collected from a national database. Individuals were separated into the AR and non‐AR groups. Eight common DDs were studied: (1) gastroesophageal reflux disease (GERD), (2) gastritis and duodenitis, (3) peptic ulcers, (4) irritable bowel syndrome, (5) gastric functional disease, (6) intestinal functional disease, (7) gastroenteritis and colitis, and (8) constipation. The rate of each DD was compared between groups. In individuals with specific DDs, the frequency of clinical visits for each DD was also compared between groups. Between users and nonusers of topical steroids in the AR group, the rate of DDs was compared. Results: Significant associations were observed between all eight DDs and AR in both sexes. In comparison to the non‐AR group, women with AR visited clinics more frequently for gastritis/duodenitis, gastric and intestinal functional disease, gastroenteritis/colitis, and constipation, while men with AR visited clinics more frequently for gastritis/duodenitis, gastric functional disease, gastroenteritis/colitis, and constipation. Female topical‐steroid users with AR had higher rates of GERD, irritable bowel syndrome, gastric or intestinal functional disease, and gastritis/colitis. Male topical‐steroid users with AR had higher rates of GERD and peptic ulcers. Conclusion: AR was associated with DDs in both sexes. However, the influence of AR on clinical visit frequency varied among specific DD groups. Topical steroid usage for AR was associated with some DDs, but the association requires future evaluation.